2016
DOI: 10.1111/ipd.12254
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status in victims of child abuse: a case–control study

Abstract: Victims of child abuse had a worse oral health status, demonstrating the need to establish special policies for oral healthcare for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 18 publications
1
36
1
7
Order By: Relevance
“…Four studies were multi-disciplinary and the remaining four papers were from nursing (n=2), psychology (n=1) and counselling (n=1). Although one study did not identify this association (Badger, 1986), Duda et al (2017), for example, found that maltreated children had a higher incidence of dental caries, missing primary teeth and untreated permanent decay. Drawing on social service data, Kvist et al (2012) identified that children in contact with social services (because of maltreatment concerns) had higher rates of dental caries, fillings in permanent teeth and missed dental appointments.…”
Section: The Study Teammentioning
confidence: 99%
“…Four studies were multi-disciplinary and the remaining four papers were from nursing (n=2), psychology (n=1) and counselling (n=1). Although one study did not identify this association (Badger, 1986), Duda et al (2017), for example, found that maltreated children had a higher incidence of dental caries, missing primary teeth and untreated permanent decay. Drawing on social service data, Kvist et al (2012) identified that children in contact with social services (because of maltreatment concerns) had higher rates of dental caries, fillings in permanent teeth and missed dental appointments.…”
Section: The Study Teammentioning
confidence: 99%
“…The mean number of untreated decayed teeth among six‐year‐old children in the UK who were under protection plans was 3.2, or 2.7 times more than that of the nonabused control group 11 . Moreover, a study in Brazil reported that the odds of dental caries among maltreated children aged 3‐15 years are 6.5 times higher, 12 leading to poorer oral health‐related quality of life 13 . While these studies emphasized immediate action to protect the oral health of maltreated children, they did not distinguish two aspects of child maltreatment (child abuse and neglect).…”
Section: Introductionmentioning
confidence: 99%
“…Early intervention is crucial, and over the past years, dental teams have received considerable attention regarding safeguarding children. Studies worldwide from the UK, Sweden, Denmark, the Netherlands, Brazil, Croatia, Greece, the United Arab Emirates, and Norway have contributed to knowledge on the report rates and factors influencing reporting suspicion, but still we lack knowledge regarding mutual collaboration and communication between CWS and general dental professionals.…”
Section: Introductionmentioning
confidence: 99%